Performance Analysis of Hybrid PDM-SAC-OCDMA-Enabled FSO Transmission Using ZCC Codes - Ammar Armghan; Meshari Alsharari; Khaled Aliqab; Mehtab Singh; Somia A. Abd El-Mottaleb (Applied Sciences, 2023)
The need for a high-speed transmission network has become essential due to the exponential increase in traffic. In this paper, a free-space-optics (FSO) link modelled by integrating two multiplexing techniques, i.e., spectral amplitude coding-optical code division multiple access (SAC-OCDMA) using zero cross correlation (ZCC) codes and polarization division multiplexing (PDM), is proposed. On the X-polarization (<semantics>XPolar</semantics>) state, three users with three different ZCC codes are transmitted. In addition, another three users with the same ZCC codes are transmitted on the Y-polarization (<semantics>YPolar</semantics>) state. Each user carries 20 Gbps of information. Weather conditions, such as clear, fog, and snowfall, are considered when assessing the efficacy of our suggested model. The results exhibit 120 Gbps transmission at 10 km under clear weather. For foggy weather, the propagation range varies from 1.6 km to 0.76 km according to the density of the fog. Moreover, the system can transport information up to 1.2 km during wet snowfall, though this range decreases to 0.26 km under dry snowfall showing that the highest attenuation is caused by dry snowfall weather conditions. The achieved ranges are obtained with a bit error rate <semantics>≤10−9</semantics> and Q-factor greater than 6. Consequently, this proposed FSO model is suggested for use in 5G and 6G high speed transmission networks.